Avaliação da dureza e módulo de elasticidade da interface de união resina – dentina utilizando a técnica de nanoindentação - Higashi, Cristian (2008)
The aim of this study was to assess the hardness and elastic modulus of resin-dentin bonding area formed by an ethanol/water-based (Adper TM Single Bond 2 [SB]) and an acetone-based system (One Step Plus [OS]), under different moisture conditions and application methods. On 24 human molars, a flat superficial dentin surface was exposed by wet abrasion. Two coats of SB or OS adhesive were applied on either a dry (D) or rewetted surface (W), under active (AA) or inactive (IA) application. After polymerization of the adhesives (600 mW/cm2/20 s), composite build-ups were constructed incrementally and specimens were stored in water (24 h). They were cross-sectioned perpendicular to the resin-dentin interface to obtain slices of 1.5 mm thickness that were embedded and polished before the test. Nanoindentations were made on composite resin, adhesive system, hybrid layer and dentin regions. The results of hardness and elastic modulus (GPa) of adhesive system and hybrid layer were analyzed by a three-way ANOVA and Tukey’s multiple comparison tests (α=0.05). The mean and standard deviation of hardness and elastic modulus values of composite resin were (1.02 ± 0.07) and (14.94 ± 0.67) respectively. In dentin, the hardness was (0.69 ± 0.10) and the elastic modulus (17.94 ± 1.84). In the adhesive layer, the highest hardness (0.38 ± 0.06) and elastic modulus (6.93 ± 0.93) of SB were obtained in W group. In this same area, the elastic modulus of OS (5.91 ± 1.12) was lowest in AA group. In the hybrid layer, the hardness of both adhesive systems was highest in AA group, however statistically significant just for OS (0.51 ± 0.2). In D group the highest hardness (0.47 ± 0.24) and elastic modulus (10.98 ± 4.65) of hybrid layer were obtained with AA. It was concluded that the active application of both adhesives in dry dentin resulted in higher hardness and elastic modulus values in the hybrid layer and the moisture increased hardness and elastic modulus values of Adper TM Single Bond 2 in the adhesive layer.